Blueprint: flexible roller conveyer / Rohana Mohd Yusof...[et al.] - Mohd Yusof, Rohana; Musa, Nur Syuhada; Musa, Nur Afiqah; Damahuri, Nur Afiqa Syaheera; Alias, Nor Afiqah (2019)
A flexible roller conveyor is one of the accommodations used to move goods from one place to another. The working scope of transporting goods from one place to another is a must for those whom work in a retailer store. However, most of the small company are having limitation of space. Therefore, they created a storage at an upper space of the store. Due to the limitation of the storage space, the employees are having health issues such as back pain, neck strains, wrist sprain and etc. Therefore, most of the employees did not working with this company for a long time as the working environment is uncomfortable for them. Our objective is to ease the work of the employees as well as to save energy and time of employees. We interviewed a few of retailer store owner and discussing on producing a new product which to help them ease the work of their employees. We also conducted a market survey to know our target market opinion on this product. We discussing and brainstorming the ideas in order to enhance our product to achieve our customer's expectation. Therefore, we come out with the idea of producing a flexible roller conveyor which can be used to transport the goods from one place to a higher place. An additional feature was added as it can be used to move goods to a higher place where the height of the conveyor can be adjusted.